Людиноподібні діалогові агенти - Chmir, Igor Alexeevich (Kamianets-Podilskyi National Ivan Ohiienko University, 2014)
The paper deals with an investigation and modeling of the inner mechanisms of human-human dialogue, with the final goal to construct an artificial humanlike dialogue agent. An ontological basis of human dialogue interaction, underlying follow-up reasoning, is obtained on the basis of analysis of human-human dialogues and illustrated by one of Plato’s dialogue, Protagoras. The paper proposes two models directed to explain some inner mechanisms of human-human dialogue. Both models are synthesized for the case of one type of human-human dialogues, called erotetic dialogue. The model of the structure of dialogue transaction is created in the context of a declarative knowledge representation, based on Language of Ternary Description. The model for the cognitive cycle of dialogue interaction is in fact a development of Neisser’s cyclical model of perception.